Using problem-based learning in college: Mastery concepts subject statistical sesearch and motivation - Ediansyah Ediansyah; Dwi Agus Kurniawan; Rahmat Perdana; Salamah Salamah (Institute of Advanced Engineering and Science, 2019)
Based on the problems obtained, the ability of students to master the subjects of research statistics is still categorized as low until this causes them to be weak in completing their final assignments. Therefore, the researchers investigated how students' mastery of the research statistical concepts and their learning motivation using learning innovations, one of which was Problem Based Learning (PBL). This research was conducted at the Islamic Education School (PGMI) Islamic State Teacher Education Institute (IAIN) Bengkulu where the sample used was semester 8th students. The research method was quantitative with a sample of 145. The research instrument was using a motivation questionnaire and multiple choice questions. The results will then be analyzed using simple regression analysis which will be presented in the form of a data table.